IDENTIDADE NACIONAL E INGLÊS LÍNGUA FRANCA: NEGOCIAÇÕES NO PROCESSO DE ENSINO E APRENDIZAGEM DE INGLÊS - Kalva, Julia Margarida (2012)
In this work we discuss Brazilian students/teacher national identity in a context of foreign language studies and the way English as a Lingua Franca is approached in the classroom. The research focus on student identity and the teaching-learning English as a Lingua Franca approach, once they are related to each other, because when it is learned-taught a new language, new identities are also presented in the classroom. With globalization, identities before seen as stables are now passing through a changing. Thus it is more difficult to say exactly who we are, that is why everything depends on where and the moment we are living. Therefore, we have as a main objective verify how English students and teacher consider themselves in a context where national identity is expressed by the language; process in which many times has the target language identity more emphasized than the local identity. This fact leads us to think about the process of teaching English as a Lingua Franca. The theoretical basis of this work is formed by Jenkins (2006), Seidlhofer (2004), Rajagopalan, regarding to English as a Lingua Franca (2003,2004), Hall (1999, 2005), Woodward (2005), Anderson (2008), talking about national identity and Pennycook (1994), Phillipson (1992), Canagarajah (1999) focusing at linguistic imperialism. The research is conducted in an English course, and participants are an English teacher and his students (intermediated level) from Universidade Estadual de Ponta Grossa; methodological procedures are basically qualitative, including a case study. Data gathered demonstrate that national identity, besides not being seen throughout the materials used for teaching, is emphasized by the teacher, situation that seems to help including teacher and students local identity in the teaching-learning process. However myths concerning teaching English as a foreign language are present in the classroom, and so, teacher and students still keep the need for following a native speaker model.